The Effect of Stray Current from Sacrificial Anode Cathodic Protection (SACP) System on the Adjacent Unprotected Reinforcing Steel. Issue 1 (March 2020) - Fonna, S; Kurniawan, R; Israr; Fachri, R; Huzni, S
Abstract: Concrete protects reinforcing steel from corrosion, but the steel may be corroded if exposed to coastal environment. Cathodic protection is a popular method to protect steel structures from corrosion. Previous researchers have conducted studies on sacrificial anode cathodic protection (SACP). However, the effect of stray current on the unprotected reinforcing steel in concrete was not reported. This study aims to analyze the effect of the stray current phenomenon on reinforcing steel which are not protected by SACP. Three types of specimens were used in the study: (1) unconnected anode-cathode, (2) connected anode-cathode, and (3) partially connected anode-cathode. The specimens were treated with 30 weeks of wet-dry cycle. Half-cell potential technique was used to measure corrosion potential. The results show that the first specimen had an average potential value of -505.44 mV, meanwhile the second specimen had average potential value -883.66 mV. According to ASTM C876 criteria, the first specimen is categorized into high corrosion risk. While, the second specimen was protected from corrosion based on NACE standard. However, the result on the third specimen shows that only the first reinforcing steel was protected from corrosion, while the other steels were categorized as severe corrosion risk level. The result on third specimen indicates that the stray current produced by SACP system could cause negative effect on the reinforcing steel by increasing susceptibility to corrosion, instead of protecting them.